CAD v1.0: Cancer Antigens Database Platform for Cancer Antigen Algorithm Development and Information Exploration - Yu, Jijun; Wang, Luoxuan; Kong, Xiangya; Cao, Yang; Zhang, Mengmeng; Sun, Zhaolin; Liu, Yang; Wang, Jing; Shen, Beifen; Bo, Xiaochen; Feng, Jiannan (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer vaccines have gradually attracted attention for their tremendous preclinical and clinical performance. With the development of next-generation sequencing technologies and related algorithms, pipelines based on sequencing and machine learning methods have become mainstream in cancer antigen prediction; of particular focus are neoantigens, mutation peptides that only exist in tumor cells that lack central tolerance and have fewer side effects. The rapid prediction and filtering of neoantigen peptides are crucial to the development of neoantigen-based cancer vaccines. However, due to the lack of verified neoantigen datasets and insufficient research on the properties of neoantigens, neoantigen prediction algorithms still need to be improved. Here, we recruited verified cancer antigen peptides and collected as much relevant peptide information as possible. Then, we discussed the role of each dataset for algorithm improvement in cancer antigen research, especially neoantigen prediction. A platform, Cancer Antigens Database (CAD, http://cad.bio-it.cn/), was designed to facilitate users to perform a complete exploration of cancer antigens online.